Komunikasi Lingkungan Berbasis Kearifan Lokal dalam Pelestarian Hutan Adat Marena di Kabupaten Enrekang-Indonesia - Harjono, Harya Ningsi; Mustafa, Mustari (Interaction: Jurnal Sosiologi Komunikasi, 2025)
This study analyses the role of local wisdom-based environmental communication in the preservation of the Marena Customary Forest in Enrekang Regency, South Sulawesi, Indonesia. Using a qualitative case study approach, data were collected from non-participant observation, in-depth interviews with 10 traditional leaders (Batu Ariri), community leaders, and conservationists, as well as analysis of traditional documents (Eda wa'ding). The results reveal three key communication patterns: (1) Ritual (offering manuk-lappa lappa to ask for ancestral permission before agricultural activities); (2) Normative (customary prohibitions such as logging/forest burning); and (3) Layered sanctions (gerek tedong pujak—slaughtering a black buffalo for serious violations). Participatory mechanisms such as Si Ottoman Upa (egalitarian decision-making with knees touching) and traditional "forest police" surveillance reinforce the system's effectiveness. This local wisdom successfully combines spiritual, ecological, and social aspects, as evidenced by sustainable practices (wood replacement: planting two seedlings per tree used). The challenges of modernisation are overcome through adaptive collaboration with the government (e.g., coffee seedling project). It is concluded that the Marena communication model offers a framework for preservation that is resistant to changing times, with recommendations for the digital codification of customary rules and their integration into national conservation policies.